2011
DOI: 10.1186/1742-2094-8-176
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective response after photodynamic therapy: Role of vascular endothelial growth factor

Abstract: BackgroundAnti-vascular endothelial growth factor (VEGF) drugs and/or photodynamic therapy (PDT) constitute current treatments targeting pathological vascular tissues in tumors and age-related macular degeneration. Concern that PDT might induce VEGF and exacerbate the disease has led us to current practice of using anti-VEGF drugs with PDT simultaneously. However, the underlying molecular mechanisms of these therapies are not well understood.MethodsWe assessed VEGF levels after PDT of normal mouse retinal tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…However, the continuous inhibition of VEGF to suppress CNV may be harmful for the surrounding tissues, as VEGF has important physiological roles in maintaining the choroidal vessels that feed the retina [58] and in supporting the survival of retinal neural cells under pathogenic conditions [59,60]. Moreover, once CNV has developed, the neural retina may be permanently damaged.…”
Section: Discussionmentioning
confidence: 95%
“…However, the continuous inhibition of VEGF to suppress CNV may be harmful for the surrounding tissues, as VEGF has important physiological roles in maintaining the choroidal vessels that feed the retina [58] and in supporting the survival of retinal neural cells under pathogenic conditions [59,60]. Moreover, once CNV has developed, the neural retina may be permanently damaged.…”
Section: Discussionmentioning
confidence: 95%
“…However, retinal neurons may have been more severely affected by changes in the microenvironment, such as cytokine and ionic changes, related to repeated macular edema over a prolonged period. Although VEGF plays a neuroprotective role [28,29], the extracellular fluid that causes edema may contain various neurotoxic cytokines that can damage the retinal neurons; previous reports have shown that levels of various inflammatory cytokines (e.g., interleukin-6 and monocyte chemotactic protein-1) were increased in the vitreous fluid of BRVO patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…Neovascularization can be suppressed with anti-angiogenic agents, such as anti-vascular endothelial growth factor (VEGF) molecules (Cheung et al, 2012, Liu et al, 2015). However, anti-VEGF therapy can also suppress normal vessel growth and neuronal survival (Suzuki et al, 2011, Sato et al, 2012). Therefore, therapeutic agents inhibiting ocular neovascularization with fewer adverse effects are desirable.…”
Section: Introductionmentioning
confidence: 99%